2018
DOI: 10.7554/elife.40958
|View full text |Cite
|
Sign up to set email alerts
|

UBE2G1 governs the destruction of cereblon neomorphic substrates

Abstract: The cereblon modulating agents (CMs) including lenalidomide, pomalidomide and CC-220 repurpose the Cul4-RBX1-DDB1-CRBN (CRL4CRBN) E3 ubiquitin ligase complex to induce the degradation of specific neomorphic substrates via polyubiquitination in conjunction with E2 ubiquitin-conjugating enzymes, which have until now remained elusive. Here we show that the ubiquitin-conjugating enzymes UBE2G1 and UBE2D3 cooperatively promote the K48-linked polyubiquitination of CRL4CRBN neomorphic substrates via a sequential ubiq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 48 publications
(59 reference statements)
4
45
0
Order By: Relevance
“…Overall, our data suggest a preference for CRL4 CRBN for UBE2G1, similar to that seen in multiple myeloma 37,38,43 .…”
Section: Inactivation Of Ube2g1 Confers Resistance To Lenalidomide Ansupporting
confidence: 80%
See 4 more Smart Citations
“…Overall, our data suggest a preference for CRL4 CRBN for UBE2G1, similar to that seen in multiple myeloma 37,38,43 .…”
Section: Inactivation Of Ube2g1 Confers Resistance To Lenalidomide Ansupporting
confidence: 80%
“…We confirmed that inactivation of UBE2G1 in PEL cells confers resistance to LEN and to POM, but not CC-122. LEN and POM resistance of UBE2G1inactivated cells was recently also reported in multiple myeloma by Sievers et al 37 and Lu et al 38 . These groups proposed a "prime-extend" mechanism, where the E2 conjugating enzyme UBE2D3 mediates neosubstrate mono-ubiquitination, while In summary, we propose a model where overall expression levels of CRBN, CUL4A, CUL4B, UBE2G1, and SENP8 dictate sensitivity of CMs in PEL (Fig 7A-C).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations